Perceived service orientation, economic factors, psychological factors and tax compliance: evidence from Nigerian SMEs - Ayuba, Augustine; Saad, Natrah; Zainal Affrin, Zaimah (Universiti Utara Malaysia, 2016)
This study examined the influence of economic and, psychological factors, as well as the moderating role of perceived service orientation on the tax compliance of Nigerian SMEs owners / managers. Three hundred and twenty one SME owners /managers participated in the survey.The Partial Least Squares (PLS) path modeling was employed to analyze the data.The results showed that the probability of detection, incentives, and the public governance quality had significant positive effects on tax compliance, while tax complexity had a significant negative effect on tax compliance.On the contrary, the results showed that tax rates and tax knowledge had no significant effect on tax compliance. Furthermore, the findings of the moderating effect revealed that perceived service orientation only moderated tax rates and incentives, while in moderating effect was discovered on the relationship between the probability of detection, tax complexity, tax knowledge and public governance quality.The implications for tax revenue authorities and other policy-makers were also discussed.